2021
DOI: 10.3390/jmse9090977
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stability and Protection Design of a Submarined Floater Platform Avoiding Typhoon Wave Impact

Abstract: This research proposes the design of a mooring system that allows the floating platform to stably dive deep enough to prevent damage induced by typhoon waves. The design principle of the mechanism is that the submarined floating platform with negative buoyancy is connected to a pontoon with positive buoyancy. The diving depth of the floating platform is determined by the rope length. If the static equilibrium of the two forces is satisfied, the diving depth will be kept. If the diving depth of the floating pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It was found that the effects of some parameters on the dynamical stability of the mooring system were significant. Lin and Chen [5] proposed the design of a submarine floating platform-towed parachute-pontoon-traction rope mooring system to prevent damage induced by typhoon waves. The dynamic stability of the in-plane motion of the mooring system possessed three degrees of freedom, and the concentrated mode was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the effects of some parameters on the dynamical stability of the mooring system were significant. Lin and Chen [5] proposed the design of a submarine floating platform-towed parachute-pontoon-traction rope mooring system to prevent damage induced by typhoon waves. The dynamic stability of the in-plane motion of the mooring system possessed three degrees of freedom, and the concentrated mode was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is no discussion in the literature [3,[5][6][7][8] on the transient responses of mooring systems. Therefore, in this study, the transient motion, stability, and rope tension of the ocean current power generation mooring system [8] with initial conditions and hydrodynamic forces and moments are analyzed.…”
Section: Introductionmentioning
confidence: 99%